Penyuluhan Hukum Mawaris Perspektif Hukum Islam sebagai Upaya Mewujudkan Kesadaran Hukum Masyarakat Desa Gayam Lor Bondowoso - Rahmat Zubandi Thahir; S.I Bahrul Ulum; Feri Kurniawan (Amaliah: Jurnal Pengabdian Kepada Masyarakat, 2024)
This community service initiative aims to improve the legal understanding and awareness of the residents of Gayam Lor Village, Botolinggo Subdistrict, Bondowoso Regency, particularly in the field of Islamic inheritance law. The background for this activity is the community’s low level of legal understanding due to limited access to education and legal information, as well as the prevalence of inheritance disputes caused by a lack of knowledge regarding the rules for the distribution of inherited assets according to Islamic law. The method used was participatory learning and action (PLA) with an approach involving interactive lectures, guided discussions, and direct Q&A sessions. The target audience for the activity included community leaders, PKK cadres, and residents of Gayam Lor Village. The results of the activity showed a significant increase in participants’ knowledge of the basic principles of Islamic inheritance law, including the identification of heirs, the distribution of inherited assets, and the differences between inheritance, wills, and gifts. Participants were also able to identify concrete cases in their communities and understand the steps for resolution in accordance with Islamic law and Indonesian legislation. The impact of these changes is evident in the increased legal awareness of the community and the reduced potential for family conflicts related to inheritance. This activity recommends the need for ongoing legal education programs and direct assistance in resolving inheritance disputes at the village level.